Methods of measuring residual stresses in components - Rossini, N.S.; Dassisti, M.; Benyounis, K.Y.; Olabi, A.G. (Materials in engineering, 2012)
► Defining the different methods of measuring residual stresses in manufactured components. ► Comprehensive study on the hole drilling, neutron diffraction and other techniques. ► Evaluating advantage and disadvantage of each method. ► Advising the reader with the appropriate method to use. Residual stresses occur in many manufactured structures and components. Large number of investigations have been carried out to study this phenomenon and its effect on the mechanical characteristics of these components. Over the years, different methods have been developed to measure residual stress for different types of components in order to obtain reliable assessment. The various specific methods have evolved over several decades and their practical applications have greatly benefited from the development of complementary technologies, notably in material cutting, full-field deformation measurement techniques, numerical methods and computing power. These complementary technologies have stimulated advances not only in measurement accuracy and reliability, but also in range of application; much greater detail in residual stresses measurement is now available. This paper aims to classify the different residual stresses measurement methods and to provide an overview of some of the recent advances in this area to help researchers on selecting their techniques among destructive, semi destructive and non-destructive techniques depends on their application and the availabilities of those techniques. For each method scope, physical limitation, advantages and disadvantages are summarized. In the end this paper indicates some promising directions for future developments.